Ранньослов’янське поселення поблизу села Хрінники Рівненської області - Козак, Д.Н.; Прищепа, Б.А. (Археологія, 2012)
Висвітлено результати досліджень селища ранніх слов’ян поблизу с. Хрінники Демидівського р-ну Рівненської обл. Визначені етапи розвитку та особливості планування селища. Работами на многослойном поселении возле с. Хринныки в уроч. Шанкив Яр Демидовского р-на Ровенской обл. в 1993—2009 гг. на площади около 8 тыс. м2 исследовано 72 объекта VІІ—Х вв. Стратиграфические наблюдения, а также анализ находок, прежде всего лепной и гончарной посуды, позволили выделить пять последовательных этапов развития селища. Существующая хронологическая схема позволяет датировать первый этап VІІ — началом VІІІ в., второй — VІІІ в., третий — ІХ в., четвертый и пятый — Х — началом ХІ в. 72 objects dated by the period from the 7th c. to the 10th c. were studied on the area of about 8 thousand m2 at the multilayer settlement in Shankiv Yar tract near Khrinnyky village of Demydivka Region in Rivne Oblast in 1993—2009. Stratigraphic observations, as well as analysis of finds, first of all of handmade and wheelmade, allowed the authors to determine five successive stages of the settlement development. The chronological scheme available makes it possible to date the first stage by the 7th c. and the beginning of the 8th c., the second one – by the 8th c., the third one – by the 9th c., and the forth and the fifth periods – by the 10th c. and the 11th c.